Chilli Anthracnose: The Epidemiology and Management - Saxena, Amrita; Raghuwanshi, Richa; Gupta, Vijai Kumar; Singh, Harikesh B. (Frontiers in Microbiology, 2016)
Indian cuisine is renowned and celebrated throughout the world for its spicy treat to the tongue. The flavor and aroma of the food generated due to the use of spices creates an indelible experience. Among the commonly utilized spices to stimulate the taste buds in Indian food, whole or powdered chilli constitutes an inevitable position. Besides being a vital ingredient of of Indian food, chilli occupy an important position as an economic commodity, a major share in Indian economy. Chilli also has uncountable benefits to human health. Fresh green chilli fruits contain more Vitamin C than found in citrus fruits, while red chilli fruits have more Vitamin A content than as found in carrots. The active component of the spice, Capsaicin possesses the antioxidant, anti-mutagenic, anti-carcinogenic and immunosuppressive activities having ability to inhibit bacterial growth and platelet aggregation. Though introduced by the Portuguese in the 17th century, India has been one of the major producers and exporters of this crop. During 2010-2011, India was the leading exporter and producer of chilli in the world, but recently due to a decline in chilli production, it stands at third position in terms of its production. The decline in chilli production has been attributed to the diseases linked with crop like anthracnose or fruit rot causing the major share of crop loss. The disease causes severe damage to both mature fruits in the field as well as during their storage under favorable conditions, which amplifies the loss in yield and overall production of the crop. This review gives an account of the loss in production and yield procured in chili cultivation due to anthracnose disease in Indian sub-continent, with emphasis given to the sustainable management strategies against the conventionally recommended control for the disease. Also, the review highlights the various pathogenic species of Colletotrichum spp, the causal agent of the disease, associated with the host crop in the country. The information in the review will prove of immense importance for the groups targeting the problem, for giving a collective information on various aspects of the epidemiology and management of the disease.